The effectiveness of SCAMPER and CoRT programs on creativity among gifted and talented students - Khawaldeh, Hamzah Mahmod Ali (2018)
The gifted and talented students possess special abilities. There is a need to enhance their special abilities, ideas and creativity. Hence, there is the need to determine and utilize creative thinking programs that develop thinking skills, their usefulness and relevance as well as their validity. However, there are limited numbers of studies, in particular on the use of SCAMPER and CoRT programs, among gifted and talented students at the King Abdullah Schools for Excellence (KASE) in Jordan. The present study examines the effectiveness of the SCAMPER and CoRT programs on creativity among the students at KASE in Jordan. The study had used quantitative and qualitative approaches. Quasi-experimental research design and tests were used to obtain the quantitative data while qualitative data was collected via semistructured interviews. The experimental group consisted of 42 students, with 21 were in the SCAMPER program group and 21 were in the CoRT program group. The control group was comprised of 21 students control group. The Torrance Test of Creative Thinking (TTCT) was used to measure students’ creativity for pretest and posttest. The research findings show a significant effectiveness of both the SCAMPER and CoRT programs on students’ creativity. However, the research findings show that there is no significant difference between the SCAMPER and CoRT programs on the students’ creativity. Analyses of the qualitative data indicate that the learning environment in KASE is different from other regular schools. This difference seemingly had contributed to positive learning process that improved students thinking ability. The research findings also provide evidence for the effectiveness of the SCAMPER and CoRT programs on the students’ creativity and flexibility in thinking. The findings in this study contribute to the knowledge about teaching within KASE in Jordan and can be used as a guide for the enhancement of learning among excellent students. This study also contributes to studies on gifted and talented students in Jordan.